2008
DOI: 10.1088/0957-0233/19/7/075302
|View full text |Cite
|
Sign up to set email alerts
|

A simple phase-encoding electronics for reducing the nonlinearity error of a heterodyne interferometer

Abstract: A phase-encoding electronics capable of compensating for the nonlinearity error in a heterodyne laser interferometer is described. The system consists of the phase demodulating electronics and the nonlinearity compensating electronics. For phase demodulation, we use the phase-quadrature mixing technique. For nonlinearity compensation, the offsets, the amplitudes and the phase of two output signals from the demodulator are adjusted electrically so that their Lissajous figure is a circle. As a result, the correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Subsequent studies of periodic error and its reduction have been reported in the literature . Researchers have analyzed and applied different methods to measure and compensate periodic error, including the frequency domain approach [1][2][3] and several time domain measure-and-compensate algorithms [39][40][41][42][43]. 6…”
Section: Periodic Errormentioning
confidence: 99%
“…Subsequent studies of periodic error and its reduction have been reported in the literature . Researchers have analyzed and applied different methods to measure and compensate periodic error, including the frequency domain approach [1][2][3] and several time domain measure-and-compensate algorithms [39][40][41][42][43]. 6…”
Section: Periodic Errormentioning
confidence: 99%
“…The main sources of nonlinearity error in heterodyne laser interferometers are non-ideal polarization of laser beam and optical parts especially polarizing-beam splitter (PBS); among these factors, non-ideal polarization namely nonorthogonality and ellipticity the polarization states of the source have the largest share in the nonlinearity error [1]. Up to now, many studies have been conducted on the effect of various factors on nonlinearity error and some methods have been presented for the nonlinearity compensation [2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…A method has been proposed for nonlinearity error compensation by Eom et al This method was based on lock-in amplifier and its advantage was the high speed of compensation, but in order to use this method, phase meter section should only be of a type of lock-in amplifier and if other methods are used, this method is ineffective [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The trends of reducing the minimum feature size, increasing wafer size and increasing throughput push the performance requirements for interferometric systems to small levels. Nowadays, the laser heterodyne interferometers are the instrument of choice for many precision machines which can be readily extended up to a resolution less than one optical wavelength [4][5][6][7]. Enhanced heterodyne displacement measurement interferometers using a three-longitudinal-mode He-Ne laserbased super-heterodyne technique were first introduced by Yokoyama in 2001 [8].…”
Section: Introductionmentioning
confidence: 99%